Learning from MacIntyre (The Lutterworth Press, James Clarke & Co Ltd, 2022)
Alasdair MacIntyre is one of the major philosophers of the late twentieth and early twenty-first century. Best known for After Virtue, first published in 1981, his output spans seven decades and has been unusually wide-ranging in its impact. As MacIntyre enters his tenth decade, this book pays tribute not just to his work, but to its influence across disciplines outside philosophy. Beginning with an intellectual biography, the chapters that follow, written by leading scholars in their fields, explore MacIntyre's contributions to theology, Thomism, moral philosophy, classical philosophy, political philosophy, Marxism, the Frankfurt School, communication, business ethics, sociology, education, law, and therapeutic method. Essential reading for scholars from across these disciplines, and for anyone who wishes to understand MacIntyre's contributions, Learning from MacIntyre not only helps readers to appreciate what we may learn from this influential thinker, but also illustrates his work's continuing significance going forward.